(untitled) (Research, Society and Development, 2021)
The present study aims to present an analysis of the flood spot caused by the hypothetical rupture of the Jazigo dam at the times of breccia formation of 0.10h, 0.30h, recommended by the National Agency for Water and Basic Sanitation (ANA) and the gap formation time of 2.15h, calculated using the Froelich equation. The structuring of the methodology consisted of the characterization of the dam; elaboration of the rupture hydrograph using HEC-HMS 4.3 software; performing the rupture simulation with the HEC-RAS 6.0 Beta software for the three gap formation times; elaboration of inundation maps of depth, velocity and intensity, with classification of alert levels; and finally, the analysis of three sites in the municipality of Serra Talhada-PE, located 7km from the dam structure. It was concluded that, for the three different training times, the intensity indicator is at the high alert level. Furthermore, the depth and velocity indicators had similar maps. In the three reference sections of the municipality, the flood wave velocity diverged more abruptly only at the time of breccia formation of 2.15h, with the height of the water level being similar between the times. Finally, it is expected to contribute to the preparation of the Emergency Action Plan for the dam, so that mitigation actions can reduce the risks of the municipality’s population in a possible rupture.